Policy strategies for value-based technology standards - Amelia Andersdotter; Lukasz Olejnik (Internet Policy Review, 2021)
Formal, government-driven technology standards developing organisations (SDOs) traditionally serve as platforms for compromise between existing national standards. In the past decade, the recognition of the driving role of SDOs in innovation has made them surface into the public debate. The influence of the work overseen by non-formal, industry-driven standards bodies including the W3C, the IETF or the IEEE is increasingly acknowledged as having both direct and indirect impacts on societies, modes of work, technology policy or politics. Starting from the European Commission's formulation of "European values", we map the interplay between enforcement of codified societal norms and industry priorities.This paper identifies policy interventions that may lead to a positive influence on the development and adoption of technology standards that bring benefit to users.
Keywords: 300; Standards; Technology policy; Accessibility; Privacy; Security; Strategy